SOSIALISASI PENGETAHUAN DAN KETERAMPILAN PENGELOLAAN HOMESTAY DI KAMPUNG SOUKOBIE DISTRIK BIAK UTARA - Sigalingging, Andy Sahat Maasi; Iriawan, Hermanu; Rudolf Leiwakabessy, Dominggus (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
The dissemination of knowledge and skills in managing tourist cottages in the context of managing tourist cottages is important to ensure operational success and business development. Homestay is a place to stay for tourists, travelers or students in a house, hosted by local families around the location. The description of the research design used to study the effectiveness of disseminating knowledge and skills is to conduct direct surveys with visitors to tourist destinations to determine their level of satisfaction with the public facilities available, and conduct observation, evaluation of current conditions. This study also emphasizes the importance of involving local communities in tourism management and management, ensuring their involvement and impact on the needs of the tourism sector because it is known that there is still a lack of transportation to tourist locations while the tourism potential consists of carving arts, dances and attractive local culinary foods. needs to be developed. Collaboration between local governments, tourism managers and local communities to increase accessibility to tourist destinations, training and education programs on environmental cleanliness and sustainability also need to be improved. The importance of continuous education and training for members of tourism awareness groups will further increase their understanding and skills in preserving the environment and local culture